Conhecimentos de usuárias e profissionais da estratégia saúde da família sobre os direitos à saúde de crianças nos primeiros 1000 dias - SILVA, Stephanie Matos (2021)
The guarantee of the right to life and health aims to provide healthy and safe birth and development, as well as decent living conditions, as investment in human development is potentially a generator of equities. The first 1000 days of a child's life refer to a critical time window for healthy growth and development, but the reality of guaranteeing rights in this period is still little known in the scientific literature. This research aimed to analyze the rights of children in the first 1000 days of life from the perspective of users and professionals of the Family Health Strategy. This is a study with a qualitative, descriptive and analytical approach carried out in the Family Health Units (USF) of a rural and quilombola municipality in northeastern Brazil, with professionals from the ESF and with pregnant women and mothers of children up to two years old. Group interviews of the focus group type were used as a data collection instrument. The sample consisted of 110 participants, 67 professionals and 43 users. Eleven groups were carried out, four with professionals with higher, technical and secondary education, three with community health workers and four with pregnant users and mothers of children up to two years old. For analysis and interpretation of the interviews, we used content analysis in the thematic modality. The rights during pregnancy and during birth are the most mentioned by the participants, with breastfeeding being the most frequent in all groups. The logistical issues and deficiencies of the health service are highlighted as hindering access to rights. Information is identified as a strategy for the promotion of rights, emphasizing knowledge as a tool for claiming and cultural issues are negatively evaluated by health professionals. The relevance of the ESF for guaranteeing children's rights is identified, highlighting the role of these services in strengthening and defending healthy growth and development.